Two new high yielding, high 'curcumin, turmeric (Curcuma longa L.) varieties- 'IISR Kedaram' and 'IISR Alleppey Supreme' - T John Zachariah, B Sasikumar, K Johnson George, K V Saji (Journal of Spices and Aromatic Crops, 2005)
Two turmeric (Curcuma longa) varieties, 'llSR Kedaram' (Acc. 126) and 'IISR Alleppey Supreme' (Acc. 585) were developed at the Indian Institute of Spices Research, Calicut, through selection and recommended for release for their high yield and curcumin content. 'llSR Kedaram', matures in 215 days and has an average yield of 5.28 t ha'] (dry rhizome) and 301.10 kg ha" curcumin whereas, 'IISR Alleppey Supreme', an Alleppey finger turmeric selection, matures in 220 days and yields 5.58 t ha'] (dry rhizome) and 309.69 kg ha" curcumin.